1966
DOI: 10.1103/physrev.148.353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transition-Metal Impurities on the Critical Temperature of Superconducting Al, Zn, In, and Sn

Abstract: The depression in critical temperature T c of several dilute solid solutions of transition elements in Al, Zn, In, and Sn was measured as a function of residual resistivity and concentration. In Zn-Mn and Zn-Cr, localized moments are present and T c decreases linearly with concentration with a slope -dT c /dc of 315 and 170°K/at.%, respectively. By comparing these numbers with theory, a value of about 1.4 eV was found for the s-d exchange integral. In all other alloys, the critical temperature is still depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(33 citation statements)
references
References 33 publications
(21 reference statements)
3
29
0
1
Order By: Relevance
“…Al 2 O 3 barriers as thin as 0.3 nm at the interface was enough to destroy the proximity effect. Also, it is observed that the T C is much higher in EuS/Al 2 O 3 /Al/Al 2 O 3 /EuS sample compared with T AP C of the EuS/Al/EuS structure, indicating less interplay between the superconductivity and ferromagnetism in the former due to the blocking of the exchange field by the barrier, whereas in EuS/Al/EuS trilayers possible unaligned Eu 2+ magnetic moments at the EuS/Al interfaces may act as magnetic impurities lowering the T C [35,36]. Given the extreme sensitivity of superconductivity to magnetic impurities, which in this case carry 7 µ B per Eu 2+ magnetic moment, T C change is not surprising.…”
mentioning
confidence: 97%
“…Al 2 O 3 barriers as thin as 0.3 nm at the interface was enough to destroy the proximity effect. Also, it is observed that the T C is much higher in EuS/Al 2 O 3 /Al/Al 2 O 3 /EuS sample compared with T AP C of the EuS/Al/EuS structure, indicating less interplay between the superconductivity and ferromagnetism in the former due to the blocking of the exchange field by the barrier, whereas in EuS/Al/EuS trilayers possible unaligned Eu 2+ magnetic moments at the EuS/Al interfaces may act as magnetic impurities lowering the T C [35,36]. Given the extreme sensitivity of superconductivity to magnetic impurities, which in this case carry 7 µ B per Eu 2+ magnetic moment, T C change is not surprising.…”
mentioning
confidence: 97%
“…T~-depression values (dTddc)inltial as high as 300 K/at~o Mn have been measured by a number of groups [16][17][18]. This is, however, more an average value.…”
Section: Introductionmentioning
confidence: 99%
“…yo copper, less than 0.1. In pure zinc the evidence from measurements of the superconducting transition temperature (Boato, Gallinaro and Rizzuto 1966) is that iron carries no moment. In figure 6(a) we use these estimates to sketch the position of the virtual bound state as a function of solvent composition; for the sake of definiteness we have chosen m, = 5 and the width of the state as 0.5 ev.…”
Section: Susceptibilitymentioning
confidence: 99%